Understanding Normal and Clinical Nutrition, 12th Edition - Sharon Rady Rolfes; Kathryn Pinna; Ellie Whitney (Cengage Learning, 2020)
This updated 12th Edition of UNDERSTANDING NORMAL AND CLINICAL NUTRITION presents the fundamentals of nutrition and nutrition therapy along with their practical applications to daily life and clinical settings. Starting with normal nutrition, the authors introduce nutrients and their physiological impacts, as well as nutritional guidelines for good health and disease prevention. Coverage of clinical nutrition includes the latest information on pathophysiology and dietary changes for treating a variety of medical conditions, from obesity and pregnancy to cardiovascular diseases, diabetes, and HIV. Known for a consistent and student-friendly narrative, the book includes systematic "How To" discussions, clinical case studies, review questions, and in-depth "Highlight" sections to help students master key topics, Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.